Enantioseparation and molecular modeling study of eight psychoactive drugs on a coated polysaccharide‐based chiral stationary phase. Issue 24 (16th September 2020) - Cai, Liangzhao; Xue, Mengyao; Lun, Jia; Li, Shuang; Yu, Jia; Guo, Xingjie
Abstract: The enantioseparation of eight psychoactive drugs has been firstly performed on a coated cellulose‐based chiral stationary phase (Chiralcel OJ‐H). To obtain optimum separation conditions, the influences of alcohol modifiers and basic/acidic additives have been studied. As a result, except for the partial separation of oxybutynin enantiomers, the other seven drug enantiomers, including mirtazapine, sulpiride, promethazine, citalopram, oxazepam, donepezil, and cyamemazine, have been completely separated. Additionally, for gaining a better insight into the chiral recognition mechanisms, molecular docking was carried out using the Autodock software. Herein, binding energy and conformations of the chiral stationary phase complexes were provided, and it was found that the distinction in enantiomeric conformation determined the number and strength of intermolecular interactions between analytes and chiral stationary phase which resulted in the difference in binding energies of two enantiomers, and ultimately led to the different migration. These modeling results were in accordance with the observed enantioseparation results in high performance liquid chromatography experiments. At last, chiral separation mechanisms have been discussed in detail, and it has been confirmed that hydrogen bond, π–π, hydrophobic interactions, and some special interactions synergistically contributed to the enantioseparation of psychoactive drugs.